Comparative effects of in-season full-back squat, resisted sprint training, and plyometric training on explosive performance in U-19 elite soccer players - de Hoyo, M.; Gonzalo-Skok, O.; Sañudo, B.; Carrascal, C.; Plaza-Armas, J. R.; Camacho-Candil, F.; Otero-Esquina, C. (The Journal of Strength and Conditioning Research, 2016)
The aim of this study was to analyze the effects of 3 different low/moderate load strength training methods (full-back squat [SQ], resisted sprint with sled towing [RS], and plyometric and specific drills training [PLYO]) on sprinting, jumping, and change of direction (COD) abilities in soccer players. Thirty-two young elite male Spanish soccer players participated in the study. Subjects performed 2 specific strength training sessions per week, in addition to their normal training sessions for 8 weeks. The full-back squat protocol consisted of 2-3 sets × 4-8 repetitions at 40-60% 1 repetition maximum (~1.28-0.98 m/s). The resisted sprint training was compounded by 6-10 sets × 20-m loaded sprints (12.6% of body mass). The plyometric and specific drills training was based on 1-3 sets × 2-3 repetitions of 8 plyometric and speed/agility exercises. Testing sessions included a countermovement jump (CMJ), a 20-m sprint (10-m split time), a 50-m (30-m split time) sprint, and COD test (i.e., Zig-Zag test). Substantial improvements (likely to almost certainly) in CMJ (effect size [ES]: 0.50-0.57) and 30-50 m (ES: 0.45-0.84) were found in every group in comparison to pretest results. Moreover, players in PLYO and SQ groups also showed substantial enhancements (likely to very likely) in 0-50 m (ES: 0.46-0.60). In addition, 10-20 m was also improved (very likely) in the SQ group (ES: 0.61). Between-group analyses showed that improvements in 10-20 m (ES: 0.57) and 30-50 m (ES: 0.40) were likely greater in the SQ group than in the RS group. Also, 10-20 m (ES: 0.49) was substantially better in the SQ group than in the PLYO group. In conclusion, the present strength training methods used in this study seem to be effective to improve jumping and sprinting abilities, but COD might need other stimulus to achieve positive effects.